Karakteristik dan Strategi Pengembangan Prasarana Air Bersih di Permukiman Nelayan Kelurahan Berbas Pantai, Kecamatan Bontang Selatan, Kota Bontang, Provinsi Kalimantan Timur - Dewi Ratih Pratiwi; Ambo Enre B. Situru; Wiwik Wahidah Osman (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2015)
Water is a very important component for human life. Water demand will continue to increase over time so that the water supply must be balanced between the needs and infrastructure of clean water. This study aims to put forward the condition of clean water infrastructure to service the needs of the community and determine strategies that can be carried out for the development of clean water infrastructure in the fishing settlements of Berbas Pantai Village. Data collection methods used include observations, questionnaires, documentation, and literature studies. The analysis methods used are analysis, qualitative descriptive, geometry, and calculation of water requirements. The results of the analysis show that the Berbas Pantai Village has a problem of clean water both raw water sources and inadequate clean water infrastructure so that a strategy to develop clean water infrastructure is needed. The strategies for developing clean water infrastructure include the addition of a PDAM network, addition of public hydrants, construction of rainwater reservoirs, addition of PDAM Bontang Municipal water discharge capacity, and a seawater treatment system using the distillation method.